Simultaneous Adsorption And Degradation Of Aniline Using Magnetic Multiwalled Carbon Nanotubes - Lim, Jia Xin (2020)
Aniline which is widely used as raw material in different industries is one of the main industrial pollutants leading to the deterioration of water quality. Thus, removal of aniline by simultaneous adsorption and degradation using magnetic multiwalled carbon nanotubes, MWCNTs-Fe3O4 was investigated in this study. MWCNTs-Fe3O4 were synthesised using direct doping method and characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy coupled with energy dispersive X-ray (SEM-EDX), Brunauer–Emmett–Teller (BET) and thermogravimetric analysis (TGA). The effects of several process parameters such as solution pH (pH 2-10), MWCNTs-Fe3O4 dosage (5-20 mg) and H2O2 dosage (4-16 mM) were studied. Solution pH of pH 6 was found to be the best for aniline adsorption while aniline degradation efficiency decreased with increasing pH. Both adsorption and degradation efficiency increased with increasing MWCNTs-Fe3O4 dosage. Adsorption was not affected by H2O2 dosage because H2O2 dosage was found to be an insignificant factor for aniline adsorption. For degradation of aniline, low H2O2 dosage (6.43 mM) was sufficient. Response surface methodology (RSM) was applied to optimize the aniline adsorption and degradation efficiency. The optimum condition was found at solution pH of 3.71, MWCNTs-Fe3O4 dosage of 14.47 mg and H2O2 dosage of 6.43 mM. The actual adsorption and degradation efficiency obtained at this condition was 59.61 % and 21.21 % respectively. It could be concluded that simultaneous adsorption and degradation using MWCNTs-Fe3O4 could be one of the feasible methods to remove aniline from wastewater.